2022
DOI: 10.3390/nu14214459
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices, Nutrition, and Associated Health Factors during the First Six Months of Life among Syrian Refugees in Greater Beirut, Lebanon: A Mixed Methods Study

Abstract: The objective was to describe infant feeding practices, nutrition and related health aspects of infants under six months among Syrian refugees in Greater Beirut, Lebanon. A cross-sectional study was conducted among Syrian refugee mothers with infants under six months in July–October 2018 (N = 114). Additionally, eleven focus group discussions were conducted to explore supportive factors and barriers associated with early breastfeeding practices. The prevalence of pre-lacteal feeding was high (62.5%), whereas e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…A significantly higher proportion of non-exclusively breastfed infants had fevers and infections and were on medications. These data confirm the importance of adequate nutrition in the first months of life, and of breastfeeding and exclusive breastfeeding [3].…”
supporting
confidence: 77%
“…A significantly higher proportion of non-exclusively breastfed infants had fevers and infections and were on medications. These data confirm the importance of adequate nutrition in the first months of life, and of breastfeeding and exclusive breastfeeding [3].…”
supporting
confidence: 77%
“…Astonishingly, the Lebanese doctors pointed out that some Syrian mothers have the conviction that lentils exacerbate anemia. This highlights the fact that adequate knowledge of a nutritious diet for young children is an important factor in preventing child anemia as demonstrated in other studies globally [ 23 , 112 ]. The key single sources of health and nutrition messages listed by the Syrian mothers were the doctors, their own mothers and social media/internet.…”
Section: Discussionmentioning
confidence: 52%
“…Previously, a study conducted in Turkey revealed that the rate of exclusive breastfeeding ≥ 6 months in Syrian babies was 28.1%, the rate of the initiation of breastfeeding within one hour was 61.4%, and all the breastfeeding indicators in Syrian refugees were lower than that for local women in Turkey [ 5 ]. In a study conducted in Lebanon, the percentages of prelacteal feeding, the initiation of breastfeeding within one hour, and the exclusive breastfeeding were 62.5%, 31%, and 24.6% respectively, in Syrian refugees [ 11 ]. It was seen that HCWs in this study perceived breastfeeding rates higher than they were in previous surveys.…”
Section: Discussionmentioning
confidence: 99%
“…According to a qualitative study conducted in Turkey, Syrian refugees think that breastfeeding negatively affects maternal health and that lactating mothers should be well-fed [ 6 ]. In a mixed-method study conducted with Syrian refugees in Lebanon, maternal health was defined as one of the barriers to breastfeeding [ 11 ]. In a qualitative study conducted in eastern Uganda, women highlighted hunger as a cause of insufficient milk production [ 13 ].…”
Section: Discussionmentioning
confidence: 99%